Identification of the opportunities and threats of using social media among Iranian adolescent girls. Issue 4 (April 2022) - Abolfathi, Mitra; Dehdari, Tahereh; Zamani-Alavijeh, Feresteh; Taghdisi, Mohammad Hossein; Ashtarian, Hossein; Rezaei, Mansour; Irandoost, Seyed Fahim
Abstract: Background: The use of the Social Media (SM) has increased dramatically among adolescents. Social media are full of opportunities and threats. The present study aims at identification of opportunities and threats of using social media among Iranian adolescent girls. Methods: This study was conducted using a qualitative approach and content analysis in 2019 in the city of Kermanshah, western Iran. Data were collected through individual semi-structured interviews and focus group discussions with 36 adolescent girls aged 12–18 years who were selected by theoretical and purposive sampling. ATLAS.ti-2019 software and Graneheim and Lundman analysis method were used to analyze the data and Guba and Lincoln criteria were used to evaluate the transferability of the results. Results: The results showed that social media is both a threat and a flourishing platform for adolescents. Findings were classified into 2 main categories and 8 subcategories: threats of using social media including 5 subcategories such as unhealthy lifestyle, increased risky sexual behaviors, academic challenges, tensions, psychological effects, and unconditional freedom, and opportunities to using social media including 3 subcategories such as psychosocial development, knowledge gain, and increased interactions. Conclusion: To strengthen social media opportunities in the face of its challenges, measures such as strengthening media literacy and teaching the correct use of the Internet and social media, educating adolescents and parents about the dangers of social media, educating and empowering parents to effectively communicate with children, producing content tailored to the cultural context and interests of adolescents, using affirmative approaches and removing access restrictions can be helpful. Abstract : Social media, Adolescent girls, Qualitative study.